HBM4EU Chromates Study: Determinants of Exposure to Hexavalent Chromium in Plating, Welding and Other Occupational Settings - Viegas, Susana (2022)
The HBM4EU Chromates study team consists of: Guillaume Antoine1, Rob Anzion2, Manuella Burgart1, Andrea Cattaneo3, Domenico Maria Cavallo3, Flavien Denis1, GiuseppeDe Palma4, Giovanni Forte5, Angela Gambelunghe7, Ogier Hanser1, Emilie Hardy6, Riikka Helenius8, Carina Ladeira9, Henriqueta Louro10, Piero Lovreglio11, Nicole Majery12, Mathieu Melczer1, Philippe Marsan1, Ana Nogueira13, Hermínia Pinhal13, Edna Ribeiro9,Jouko Remes8, Sílvia Reis Santos13, Françoise Schaefers6, Marta Senofonte5, Sally Spankie14, Maurice van Dael2, Henna Veijalainen8, with the correspondent affiliations: 1French National Research and Safety Institute, Vandoeuvre-les-Nancy, France; 2Radboud Institute for Health Sciences, Radboudumc, Nijmegen, The Netherlands; 3Department of Science and High Technology, University of Insubria, Como, Italy; 4Department of Med-ical and Surgical Specialties, Radiological Sciences, and Public Health, University of Bre-scia, Brescia, Italy; 5 Department of Environment and Health, Istituto Superiore di Sanità, Rome, Italy; 6 Department Health Protection, Laboratoire National de Santé (LNS), 1, Rue Louis Rech, 3555 Dudelange, Luxembourg; 7Department of Medicine and Surgery, Uni-versity of Perugia, Perugia, Italy; 8Finnish Institute of Occupational Health, Helsinki, Fin-land; 9H&TRC-Health & Technology Research Center, ESTeSL-Escola Superior de Tecnologia da Saúde de Lisboa, Instituto Politécnico de Lisboa; Comprehensive Health Research Center (CHRC), 1169–056 Lisbon, Portugal; 10National Institute of Health Dr. Ricardo Jorge, Department of Human Genetics, Lisbon and ToxOmics –Centre for Toxi-cogenomics and Human Health, NOVA Medical School, Universidade NOVA de Lisboa, Lisbon, Portugal; 11Interdisciplinary Department of Medicine, University of Bari, Bari, Italy; 12Service de Santé Au Travail Multisectoriel (STM), Luxembourg; 13National Institute of Health Dr. Ricardo Jorge, Environmental Health Department, Lisbon, Portugal; 14Institute of Occupational Medicine (IOM), Edinburgh, EH144AP, UK.